ChemInform Abstract: Multicomponent Cascade Reactions of Unprotected Carbohydrates and Amino Acids. Issue 41 (October 2015) - Voigt, Benjamin; Linke, Michael; Mahrwald, Rainer
Abstract The Ugi‐type reaction of carbohydrates such as (I), amino acids, and ethyl isocyanoacetate allows the synthesis of novel glycopeptide structures.